Development of Visual Literacy-Based Learning Media to Enhance Writing Skills of Second Grade Elementary Students - Turmudli, Turmudli; Sumarno, Sumarno; Buchori, Achmad (Journal of Educational Sciences, 2025)
Writing is one of the essential literacy skills required in early elementary education. However, many second-grade students struggle to develop ideas, sequence events, and construct coherent sentences when writing narrative texts. Therefore, this study aimed to develop a visual literacy-based learning media to improve the writing skills of second-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The media was designed in the form of interactive sequential picture panels to help students generate ideas and structure their writing based on visual cues. Validation was conducted by media and material experts, while product trials involved teachers and students at SD Negeri Pasucen in the 2024/2025 academic year. The media received a validity score of 87.5% from media experts and 88.3% from material experts, indicating that it was highly valid. Practicality results showed scores of 89.6% from teachers and 86% from students, categorized as very practical. Effectiveness testing revealed significant improvement, with an N-Gain of 79.08% (p < 0.05). In conclusion, the media is valid, practical, and effective in improving students’ narrative writing skills.